2002
DOI: 10.1362/0267257022775864
|View full text |Cite
|
Sign up to set email alerts
|

The Social Construction of New Marketing Paradigms: The Influence of Personal Perspective

Abstract: Marketing is no stranger to "big new ideas" which purport to be new paradigms for the study of the discipline. Relationship marketing, one-to-one

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 43 publications
0
39
0
2
Order By: Relevance
“…The building of such a brand image is often 'artificial', in the sense that it relies more on the perception of consumers than reality itself. In a developed world dominated by media and other communication channels, perception often becomes a more critical parameter than reality itself (Palmer and Ponsonby, 2002;Naumann et al, 2001). Businesses realize this fact and on average spend a large percentage of their income in efforts to shape perception (and therefore preferences) through advertising and other means of communication with the consumer.…”
Section: Effect Of Developed Countries' Contemporary Consumer Behaviomentioning
confidence: 99%
“…The building of such a brand image is often 'artificial', in the sense that it relies more on the perception of consumers than reality itself. In a developed world dominated by media and other communication channels, perception often becomes a more critical parameter than reality itself (Palmer and Ponsonby, 2002;Naumann et al, 2001). Businesses realize this fact and on average spend a large percentage of their income in efforts to shape perception (and therefore preferences) through advertising and other means of communication with the consumer.…”
Section: Effect Of Developed Countries' Contemporary Consumer Behaviomentioning
confidence: 99%
“…As explained in earlier sections of this paper, DMO is a personally derived and directed perspective on marketing imperatives, and the nature of its development acknowledges Palmer and Ponsonby"s (2002) view that both research endeavour and theory are largely socially constructed. There is, in reality, no "best" way to pursue the broad agendas explored in this paper, and other, non-DMO, perspectives -focusing on which marketer/market characteristics might be of most empirical interest -would be equally valuable.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Or are they, as Woodall (2004) hypothesises, still essentially "hard-wired to the hard-sell"? Palmer and Ponsonby (2002) suggested that despite a plethora of new marketing manifestos, marketing on the ground is pretty much still the way it has always been, whilst much of the recent output from Ulster"s Stephen Brown (from Brown, S. 1999, through to Brown, S. 2005) essentially reassertsrightly or wrongly -stereotypical marketing characteristics and behaviours.…”
Section: Marketing and The Marketermentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of perceived value has been extended to include mixed dimensions, for example; intrinsic and extrinsic value by Babin, Darden, & Griffin (1994) and Novak, Donna, & Duhachek (2003); the six-facet value of "PERVAL" by Sweeney and Soutar (2001); and the five consumption dimensions by Sheth et al, (1991 Table 1 summarizes the authors who have chosen the multidimensional approach and the dimensions of the construct for perceived value. All the researchers have the two common fundamental dimensions of perceived value: functional and affective (Anderson & Narus, 1990;Gassenheimer, Houston, & Davis, 1998;Lapierre, 2000;Sweeney & Soutar, 2001;Palmer & Ponsonby, 2002). The functional dimension indicates the reasonable and economic assessments generated by individuals.…”
Section: Measuring Perceived Valuementioning
confidence: 99%